Acquisition of Writing Skills by Adult Migrant Learners of Spanish - Chao Garcia, Javier; Mavrou, Irini (LESLLA Symposium Proceedings, 2021)
The aim of the study was to identify the most common error types and spelling strategies in the written productions of 43 adult migrant learners of Spanish who took the Diploma LETRA exam. The results showed a clear prevalence of morphostructural errors and of phonetic and phonemic strategies. Length of stay in Spain was negatively correlated with the number of morphostructural errors and the number of words, while age was positively correlated with the number of morphostructural and total errors. Neither gender nor education level in the first language appeared to have an influence on the linguistic variables of the study.